2018
DOI: 10.1016/j.aott.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich fibrin on epidural fibrosis and comparison to ADCON® Gel and hyaluronic acid

Abstract: We concluded that PRF contributed to hemostasis and prevented epidural fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Therefore, studies to prevent epidural fibrosis formation in recent years have gained importance. [ 3 , 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, studies to prevent epidural fibrosis formation in recent years have gained importance. [ 3 , 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Cytokines released into the environment in epidural fibrosis such as interleukin (IL)-6, IL-8, transforming growth factor beta (TGF-β), and tumor necrosis factor alpha (TNF-α) induce the pathological process by affecting the fibroblasts and, thereby, leading to the formation of granulation tissue in the hematoma in the surgical area. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelet-rich fibrin (PRF), acting as a barrier due to its membranous structure, not only controls fibroblast migration to the wound area but also reduces adhesion by controlling collagen synthesis. Demirel compared the effects of Adcon-L and PRF on EF using 28 Sprague-dawley rats and showed that the PRF group developed lower EF than the Adcon gel group [29].…”
Section: Discussionmentioning
confidence: 99%